KINERJA KOMISI PENYIARAN INDONESIA DAERAH (KPID) SULAWESI UTARA DALAM PENGAWASAN PEMBERITAAN DAN IKLAN KAMPANYE PEMILIHAN GUBERNUR DAN WAKIL GUBERNUR SULAWESI UTARA TAHUN 2024 - Stefani Runtukahu; Daud M Liando; Maxi Egeten (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2026)
news and campaign advertisements for the 2024 Governor and Deputy Governor elections. Broadcasting occupies a central position as a crucial pillar in the democratic system, functioning as the main channel for distributing information to the public, including during the Regional Head Election (Pilkada) process. Broadcast media has great power in shaping and influencing public perceptions of political candidates. Therefore, neutrality, fairness, and balance of information presented are absolute prerequisites for the creation of a healthy and accountable political process. Law 32 of 2002 concerning Broadcasting in Article 4 paragraph 1 mandates that Broadcasting aims to strengthen National Integration, foster the character and identity of a faithful and pious nation, educate the life of the nation, advance general welfare in order to build an independent, democratic, just and prosperous society. KPID carries out supervisory functions for broadcasting institutions, including imposing sanctions and establishing coordination and cooperation with the government, broadcasting institutions, and the public. This research uses qualitative research methods. The research results show that, based on analysis using the performance theory proposed by Dwiyanto, this study concludes that the performance of the North Sulawesi KPID in overseeing news and campaign advertisements for the 2024 gubernatorial and vice gubernatorial elections was good, although not yet at ideal levels. Judging from its performance, the North Sulawesi KPID was actively involved in every stage of the 2024 gubernatorial and vice gubernatorial elections